Pengaruh Pengumuman Peringkat Obligasi Dan Peringkat Sukuk Perusahaan Terhadap Abnormal Return Saham Di Indonesia - Nurjanah, Siti; , Dr. Triyono, SE, M.Si (2016)
The purpose this research is to explain the effect of announcement of bond rating and announcement of sukuk rating to abnormal return. The population in this study is all of announcement of bond rating and announcement of sukuk rating of companies that launch bond, sukuk and stock during the year 2011-2015. The sample selected based on purposive sampling is 52 announcement for bond ratings and 34 announcement for sukuk ratings. This study is an event study research using market adjusted model with 11 days of windows period (t-5 to t+5). The data used in this reseach is daily closing price that is colleced by documentation method. Analysis methods used in this research are normality test, one-sample t-test, and paired t-test. The results of this study find that generally no influence announcement of bond rating to abnormal return, abnormal return just happened on the second day after announcement. While for announcement of sukuk rating does not change abnormal return well before the announcement, the announcement, and after announcement. Abnormal return does not reaction significance differeence between the return before and afther the announcement of bond rating and announcement of sukuk rating.